Permanent Neonatal Diabetes Caused by Dominant, Recessive, or Compound Heterozygous SUR1 Mutations with Opposite Functional Effects - Ellard, Sian (American Society of Human Genetics, 2007)
Heterozygous activating mutations in the KCNJ11 gene encoding the pore-forming Kir6.2 subunit of the pancreatic beta cell K(ATP) channel are the most common cause of permanent neonatal diabetes (PNDM). Patients with PNDM due to a heterozygous activating mutation in the ABCC8 gene encoding the SUR1 regulatory subunit of the K(ATP) channel have recently been reported. We studied a cohort of 59 patients with permanent diabetes who received a diagnosis before 6 mo of age and who did not have a KCNJ11 mutation. ABCC8 gene mutations were identified in 16 of 59 patients and included 8 patients with heterozygous de novo mutations. A recessive mode of inheritance was observed in eight patients with homozygous, mosaic, or compound heterozygous mutations. Functional studies of selected mutations showed a reduced response to ATP consistent with an activating mutation that results in reduced insulin secretion. A novel mutational mechanism was observed in which a heterozygous activating mutation resulted in PNDM only when a second, loss-of-function mutation was also present.